Compositional characterization of Etruscan earthen architecture and ceramic production. (2nd July 2020) - Ceccarelli, L.; Moletti, C.; Bellotto, M.; Dotelli, G.; Stoddart, S.
Abstract : This study presents the results of new research into Etruscan technology for earthen architecture as well as ceramic production in the upper Tiber Valley in central Italy, using as a case study the Etruscan settlement of Col di Marzo (Perugia). It determines the compositional differences of the raw material employed as building material and for ceramic production by X‐ray powder diffraction (XRD), thermogravimetric analysis and differential thermal analysis (TG‐DTG), Fourier‐transform infrared analysis (FTIR) and geotechnical analyses. The research also advances the knowledge of ceramic manufacturing technology, with a focus on impasto production, at Col di Marzo between the fifth and mid‐third centuries bce and the surrounding territory on the left bank of the River Tiber. The compositional analysis of building material compared with the ceramics provides answers to questions related to their sourcing and deepens the understanding of the exploitation of natural resources.